Ägyptens wirtschaftliche Grundlagen in der Mittleren Bronzezeit - Nutz, Rainer, (Archaeopress Egyptology ;, 2014)
Economic issues are seemingly neglected topics within Egyptology. This study attempts to highlight selected economic aspects of the first half of the second millennium BC.